Pulmonary infiltrates–diagnostic problems in lymphoma. Issue 770 (December 1989) - Campbell, J. H.; Raina, V.; Banham, S. W.; Cunningham, D.; Soukop, M.
Abstract : The use of invasive investigations in immunocompromised patients with pulmonary infiltrates is controversial. We report a series of 22 pulmonary lesions occurring in 19 patients with underlying Hodgkin's (7) and non-Hodgkin's (12) lymphoma in whom invasive investigations were performed. The principle techniques used were fibreoptic bronchoscopy, bronchoalveolar lavage and transbronchial lung biopsy. A specific diagnosis was made on 12 occasions (55%). Involvement of the lung with lymphoma (6) and cytotoxic drug induced pneumonitis (4) were the commonest diagnoses, infection being found on only one occasion. In 15 of these 22 procedures (68%) the information obtained made a positive contribution to patient management.